2016
DOI: 10.1103/physreva.93.023418
|View full text |Cite
|
Sign up to set email alerts
|

Many-electron effects on x-ray Rayleigh scattering by highly charged He-like ions

Abstract: The Rayleigh scattering of x-rays by many-electron highly charged ions is studied theoretically. The manyelectron perturbation theory, based on a rigorous quantum electrodynamics approach, is developed and implemented for the case of the elastic scattering of (high-energetic) photons by helium-like ion. Using this elaborate approach, we here investigate the many-electron effects beyond the independent-particle approximation (IPA) as conventionally employed for describing the Rayleigh scattering. The total and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…In order to investigate the many-body effects beyond the IPA, we have recently applied the rigorous quantum electrodynamics approach. Based on this approach we have shown that the electron-electron interaction effects do not exceed 3%−4% for both the angular distribution and the linear polarization of the scattered photons [64]. In the angular region of the present experiment ( 65  q ) we do not expect significant effects which arise from the solid state of the scattering target (compared to the scenario of an isolated atom which is assumed in the theory discussed above).…”
Section: Resultssupporting
confidence: 48%
“…In order to investigate the many-body effects beyond the IPA, we have recently applied the rigorous quantum electrodynamics approach. Based on this approach we have shown that the electron-electron interaction effects do not exceed 3%−4% for both the angular distribution and the linear polarization of the scattered photons [64]. In the angular region of the present experiment ( 65  q ) we do not expect significant effects which arise from the solid state of the scattering target (compared to the scenario of an isolated atom which is assumed in the theory discussed above).…”
Section: Resultssupporting
confidence: 48%
“…That means that the electron-nucleus interaction is incorporated in the unperturbed Hamiltonian of the system and the ion-photon interaction is considered as perturbation. For the determination of the properties of the scattered light, we then evaluate the second-order scattering operatorM, the matrix elements of which are defined as (in units h = m e = c = 1) [11,27]:…”
Section: General Theory Of Transition Matrix Amplitudementioning
confidence: 99%
“…Within the class of piecewise polynomials, B-splines (for details, see [34]) are especially well suited for atomic physics numerical tasks [35,37], and that is why they are used here as well. In the works [11,38], the B-splines basis set was also employed for the calculation of the Rayleigh scattering.…”
Section: Exact Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various non-linear (second- as well as higher-order perturbation) processes have been observed during the past years but could often not be calculated in good detail for many ions, atoms or molecules of interest. Well-known second-order processes of this sort include, for instance, the multi-photon absorption and emission [ 1 , 2 , 3 ], the resonant [ 4 ] and two-photon ionization [ 5 , 6 ], the radiative and double Auger emission of atoms [ 7 , 8 ] and molecules [ 9 ], their (single-photon) double ionization [ 10 , 11 , 12 ] or the Rayleigh and Raman scattering of light [ 13 , 14 , 15 ], to name just a few. Until the present, however, most of these processes are not yet (well) understood quantitatively since, in perturbation theory, each additional order (beyond the first-order) typically requires an implicit summation (integration) over the full spectrum of the system.…”
Section: Introductionmentioning
confidence: 99%